2023
DOI: 10.1080/21645515.2023.2281737
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective audit of neonatal BCG vaccination in Grampian, Scotland

Saba Savul,
Susan Duthie

Abstract: Bacillus Calmette–Guerin (BCG) vaccine confers protection against tuberculosis (TB) and works most effectively when given to infants. Scotland runs a risk-based program in which BCG vaccine is offered to infants whose parent or grandparent was born in a high incidence country for TB. BCG vaccination records for all infants born in Grampian from 1st January 2019 to 31st December 2021 were reviewed from Nov 2022 to Feb 2023. Three electronic databases were examined, i.e. BadgerNet, Scottish Immunisation Recall S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Finally, a recent audit conducted by Savul & Duthie 24 revealed that the BCG vaccination rate for newborns in a Scottish region was roughly 90% for three consecutive years. This is an improvement from previous periods.…”
mentioning
confidence: 99%
“…Finally, a recent audit conducted by Savul & Duthie 24 revealed that the BCG vaccination rate for newborns in a Scottish region was roughly 90% for three consecutive years. This is an improvement from previous periods.…”
mentioning
confidence: 99%